Metabonomic study of the protective effect of Fukeqianjin formula on multi-pathogen induced pelvic inflammatory disease in rats - Yan Zhang; Wei Li; Liang Zou; Yun Gong; Peng Zhang; Shasha Xing; Hang Yang (BMC, 2018)
Abstract Background Fukeqianjin formula has been effectively used in the treatment of pelvic inflammatory disease (PID) and the related complications in clinic. Although there have been some studies about the underlying mechanism that focus on its anti-inflammatory and immunoregulatory activities. But the mechanism is still not fully understood. The aim of this study was to investigate the alteration of plasma metabolic profiles in PID rats and the regulatory effect of Fukeqianjin formula on potential biomarkers. Methods Pelvic inflammatory model was established by intrauterine inoculation of multiple pathogens combined with mechanical injury of endometrium. Rats were randomly divided into normal group, model group, azithromycin group, high-and low-dose of Fukeqianjin formula treatment group (FF-H, and FF-L, respectively). After 14 days of intragastric administration, the plasm levels of interleukin-1β (IL-1β) and nitric oxide (NO) were measured. To further recognize and identify potential biomarkers and metabolic pathways, an ultra-performance liquid chromatography-quadrupole-Exactive Orbitrap-mass spectrometry (UPLC-Q-Exactive Orbitrap-MS) metabonomic method combined with multivariate analyses including principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA) and orthogonal partial least squares discriminant analysis (OPLS-DA), was employed to analyze the metabolic profiling. Results Compared with normal group, the plasma levels of IL-1β and NO were significantly increased in the PID model group (P < 0. 05), and obviously decreased after high-dose intervention of Fukeqianjin formula (P < 0. 01). The PCA, PLS-DA and OPLS-DA analysis showed that PID rats were clearly separated from normal rats. Compared with the PID model group, the metabolite profiles of Fukeqianjin formula treatment group was gradually restored to normal. Meanwhile, 14 potential metabolite biomarkers, which were mainly related to the metabolic pathways of intervening glycerophospholipid metabolism, linoleic acid metabolism/alpha-linolenic acid metabolism, amino acid metabolism, arachidonic acid metabolism, and unsaturated fatty acids biosynthesis, have been identified. Fukeqianjin formula exerts good regulatory effect on the abnormal metabolism of PID rats. Conclusions Intrauterine inoculation of multiple pathogens combined with mechanical injury of endometrium could significantly disturb the plasma metabolic profiles of rats. Fukeqianjin formula has potential therapeutic effect on multi-pathogen-induced PID by ameliorating metabolism disorders and alleviating the inflammatory response.